Universidad y sociedad: notas para un debate. - Azpeitia Arman, Mª Concepción; Gutiérrez Fernández, Juan; Gómez Colilla, Esther; Delgado Moreira, Juan Manuel (Cuadernos de Trabajo Social, 1993)
Sin resumen